2022
DOI: 10.1002/biot.202200062
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of the CMV promoter for controlled expression of recombinant genes in HEK293 cells

Abstract: Expression of recombinant genes in HEK293 cells is frequently utilized for production of recombinant proteins and viral vectors. These systems frequently employ the cytomegalovirus (CMV) promoter to drive recombinant gene transcription. However, the mechanistic basis of CMV-mediated transcriptional activation in HEK293 cells is unknown and consequently there are no strategies to engineer CMV for controlled expression of recombinant genes. Extensive bioinformatic analyses of transcription factor regulatory elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In the CMV subnetwork ( Supplementary Figure 4A ), we found that eight out of nine CMV-specific cytokines were targeted by REL, which indicates its key function in CMV CD8 + Tm cells. REL is a subunit of the NF-κB family, and many studies suggest that the activation of CMV is related to the activity of REL ( 40 , 41 ). In total, there were 3,100 CD8 + Tm cells denoted as “REL regulon” active in our data according to the AUCell score (with 0.14 as cutoff) ( Figure 5B ), and most of them were CMV-specific Temra cells ( Supplementary Figure 4D ), which is in line with cytokine expression in our previous results ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…In the CMV subnetwork ( Supplementary Figure 4A ), we found that eight out of nine CMV-specific cytokines were targeted by REL, which indicates its key function in CMV CD8 + Tm cells. REL is a subunit of the NF-κB family, and many studies suggest that the activation of CMV is related to the activity of REL ( 40 , 41 ). In total, there were 3,100 CD8 + Tm cells denoted as “REL regulon” active in our data according to the AUCell score (with 0.14 as cutoff) ( Figure 5B ), and most of them were CMV-specific Temra cells ( Supplementary Figure 4D ), which is in line with cytokine expression in our previous results ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…The same TFREs sequence plays different roles in different cell lines and the function of the synthetic promoter can be tested in different cell lines. Regulation of promoter activity is highly cell-type specific, as different cells contain different transcription factors and co-regulatory factor [ 19 , 32 ], In addition, synthetic promoters with reduced promoter interference effects can be designed for the expression of multiple genes on a single vector by constructing promoters containing different TFREs types.…”
Section: Discussionmentioning
confidence: 99%
“…The strong human cytomegalovirus major immediate early gene (CMV) promoter is widely applied to express the GOI in CHO cell system. However, CMV promoter is inherently prone to silencing, leading to drop in yield during long-time expression [ [19] , [20] , [21] , [22] , [23] , [24] ]. The CMV promoter mainly consists of an upstream regulatory sequence (URS), CMV enhancer, core polymerase II promoter, first exon, and intron A [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…37 Currently, studies on the transcription of recombinant genes driven by cytomegalovirus (CMV) promoters have been used to produce recombinant proteins and viral vectors. 72 Using liver cells as the chassis, the host liver is reprogrammed to guide the synthesis and self-assembly of small-interfering RNA (siRNA) into secretory exosomes, thereby promoting siRNA delivery in vivo . Zhang's group utilized this in vivo siRNA delivery platform to target key pathogenic genes for lung cancer (EGFR/KRAS), glioblastoma (EGFR/TNC), obesity (PTP1B), 73 and Huntington's disease (mHTT), 74 with significant therapeutic effects observed.…”
Section: Self-assemblymentioning
confidence: 99%